THE INFLUENCE OF LAYOUT ON EMPLOYEE JOB SATISFACTION AT PT KERETA API INDONESIA (PERSERO) DAOP 4 SEMARANG - Nugroho, Jati; Damayanti, Herlin (Universitas YPPI Rembang, 2024)
The purpose of this research were to fine out Layout (X) on Employee Job Satisfaction (Y) PT Kereta Api Indonesia (Persero) Daop 4 Semarang. The methods of data collection used in this research are observation, questionnaires and literature study. The questionnaires used a Likert scale with 4 rating score scale and the sample in this study were 40 employees’ of the PT Kereta Api Indonesia (Persero) Daop 4 Semarang. The analysis tools used are test of validity , reliability test, T test, simple linear regression and the coefficient of determination. Based on the calculation using SPSS version 25, the results of this research shows that the regression equation Y = 4,811 + 0,789x and the T test results stated that Layout (X) t count was bigger than t table and has a significant bigger than level significance, so the Layout variable have a significant positive influence to The Employee Job Satisfaction. While from the result of determination coefficient (Adjusted R Square) showed that 0,582 or 58,2% of the independent variable were Layout. It means that 58,2% of employee job satisfaction was explained by Layout. While 41,8% was explained by other factors not examined in this research.Keywords: Employee Job Satisfaction and Office Layout